STATISTICAL ASSESSMENT OF THE CONFIDENCE INTERVAL OF THE AVERAGE PROFIT OBTAINED IN A MONTH BASED ON SURVEYS (American Journal of Business Management, Economics and Banking, 2025)
The article discusses the issues of collecting and processing statistical data for statistical evaluation based on surveys regarding the confidence interval of the average profit of industrial enterprises over a month.